PENGARUH LUAS LAHAN SAWAH IRIGASI TERHADAP PRODUKSI BERAS DI INDONESIA - Arif Budi Satrio; Suprapti Supardi; Sri Wahyuningsih (Universitas Wahid Hasyim, 2008)
In Indonesia, the wide of irrigation wetland about 70 % of totality rice production area, eventhough the level of production about 85% of totality rice production area. At present and future, irrigation wetland being more scarcity, eventually in Java and Bali, this case, becaused of incresing competition on area and water utilities for non agricultural interest. For Indonesia, the tends of wetland area scarcity espesially in Java to go straight on and there is no effective regulation or action to be done by local community to control area conversion. This research purposes to know the influence of the wide irrigation wetland area to rice production in Indonesian's big islands, except Maluku and Papua, also national scale from 1994-2004. This research uses descriptive analitic method. The secundary data are used, collected, arranged then analized with Cobb-Douglas regression. Refers to the analisis results and the discussion of each hipotesis, we know that on Į = 10%, the wide of wetland irrigation area on Java, Bali and Nusa Tenggara are significant influencing to rice production. Eventhough in Sumatera, Kalimantan and Sulawesi , the wide of irrigation wetland area were not significant influencing to rice production. The significant influence of the wide of irrigation wetland area in Java and Bali ± Nusa Tenggara refer to BMG (2006) becaused of in dry season almost irrigation wetland area were cultivated by paddy. Eventhough the no significant influence of the wide of irrigation wetland area in Sumatera, Kalimantan, Sulawesi also national scale refer to BMG (2006) becaused of in dry season almost the irrigation wetland area were not cultivated by paddy. Knowing the importance of the wide irrigation wetland area to rice production, expected to local communities and local goverments to take care the area, so the area conversion not happen again. For making new irrigation wetland area must be supported by deep research and involve a lot of experts from conecting sectors. Base on this research, be expected, research can be developed by another researcher in order to usefull to this nation.Key words : Irrigation wetland Area, Area Conversion, Making New Wetland, Dry season, Rice production.